Isolated Cerebral Alveolar Echinococcosis. (14th December 2018) - Baldolli, Aurélie; Bonhomme, Julie; Yera, Hélène; Grenouillet, Frederic; Chapon, Françoise; Barbier, Charlotte; Hazera, Pascal; Verdon, Renaud
Abstract: Cerebral alveolar echinococcosis (AE) is rare and mostly associated with liver involvement. We report an exceptional case of a 62-year-old man with a hereditary hemorrhagic telangiectasia harboring a primary cerebral AE mimicking neurocysticercosis with >100 cerebral lesions and without liver involvement.